2019
DOI: 10.1039/c9qo00750d
|View full text |Cite
|
Sign up to set email alerts
|

nBuLi-promoted anti-Markovnikov selective hydroboration of unactivated alkenes and internal alkynes

Abstract: A novel anti-Markovnikov selective hydroboration of alkenes and alkynes with HBpin using nBuLi as an effective initiator is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…The nucleophilic motifs can be separated into three classes: pre-catalyst activators, [15][16][17][18][19][20][21][22] sacrificial ligands [23][24][25] and inherent nucleophilic catalysts (Scheme 1C). [26][27][28][29][30][31] To distinguish between 'true' catalysis and BH3 catalysis for reactions using HBpin it was necessary to: 1. Identify nucleophile-promoted BH3 formation.…”
Section: Hidden Boron Catalysis: Nucleophile-promoted Decomposition Of Hbpinmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleophilic motifs can be separated into three classes: pre-catalyst activators, [15][16][17][18][19][20][21][22] sacrificial ligands [23][24][25] and inherent nucleophilic catalysts (Scheme 1C). [26][27][28][29][30][31] To distinguish between 'true' catalysis and BH3 catalysis for reactions using HBpin it was necessary to: 1. Identify nucleophile-promoted BH3 formation.…”
Section: Hidden Boron Catalysis: Nucleophile-promoted Decomposition Of Hbpinmentioning
confidence: 99%
“…Likewise, NaHBEt3 has been used as an activator and was observed to promote BH3 formation (Entry 7). [21][22] Alkoxides, amides, NaOH, n Bu2Mg, n BuLi and LiAlH4 have all been proposed to be active hydroboration catalysts [26][27][28][29][30][31] or used as sacrificial ligands. [23][24][25] All promoted BH3 formation (Entries 8-13).…”
Section: Scheme 1 the Roles Of Nucleophiles And Bh3 In Hydroboration Catalysismentioning
confidence: 99%
“…144 Precatalyst 34 (7-10 mol%) with HBpin catalyzed the hydroboration of a broad range of alkynes at 80 C with wide functional compatibility to alkoxy, amino, halide, alkenyl, and hydroxy groups, giving the b-trans-vinylboronate esters in good to high yields (Scheme 51). As observed in the lithium catalysis, 141 the regioselectivity in the case of unsymmetrical internal alkynes was improved from 1.5 : 1 up to >99 : 1 by increasing the differential steric effect of the substituents (R and R 0 ).…”
Section: Hydroborationmentioning
confidence: 59%
“…Together with the transition metal-free organocatalysts for the hydroboration of alkynes, environmentally benign and commercially useful main-group catalysts based on Al, 90,[130][131][132][133][134][135][136][137][138][139] Li, [138][139][140][141][142] and Mg 143,144 have been recently developed as alternatives to transition metal catalysts. 145 In 2016, Roesky et al reported the cis-hydroboration of alkynes catalyzed by a neutral DEP NacNacAlH 2 (18).…”
Section: Hydroborationmentioning
confidence: 99%
“…Nevertheless, Bao and Shi recently expanded its utility in the hydroboration of allylic alcohols, 120 alkenes, alkynes, and imines. 121,122 Meanwhile, An and co-workers disclosed an example of hydroboration of aldehydes and ketones in the presence of sodium hydride at rt, to give corresponding alcohols (after hydrolysis) in almost quantitative yields (Scheme 16). 123 A considerable drawback of this protocol is again connected to the sensitivity of the catalyst.…”
Section: Hydroboration Of Unsaturated Carbon-heteroatom (O N) Moietiesmentioning
confidence: 99%